Investigating electron-transfer processes of supramolecular donor-acceptor complexes using femtosecond transient absorption spectroscopy - Kruger, T.P.J. (Tjaart) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.